Early Medieval Icons-Pendants. Model-Pieces and Imitations - Sobolev, Vladislav Yu. (Actual Problems of Theory and History of Art, 2019)
Objects of personal devotion originating from archaeological excavations of ancient Russian monuments are of great importance for analyzing the history of the development of artistic thought, understanding Christian images and the ways of their distribution. Serial popular objects that evoke dimitation and served as master models for secondary castings indicate the formation and spread of the all-Russian traditions of honoring certain saints. The earliest and reliably dated icons-pendants with mounted St. George were found in Novgorod, which, perhaps, was the center from where they spread across the territory of North and West Russia, up to Latgale and Eastern Poland.Pendants with the composition “The Dormition of the Virgin Mary” on one side also belong to rather mass types of ancient Russian devotional objects. It was believed that they were associated with the Dormition Cathedral in Vladimir, erected in the middle of the 12th century by Prince Andrei Bogoliubsky. New finds of alarge series of similar medallions on the territory of Ukraine cast doubt on the existence of a single center for their production, which was located in Northeast Russia. The distribution of personal devotional objects in the Old Russian territory clearly reflects the existence of both common traditions that overcame internal and external borders, as well as local cults.